The Effect of Equity Compensation on Turnover Intention by Work Dedication and Work Absorption as an Intervening Variable (Study on Honorary Nurse at IA Moeis Hospital Samarinda) - Timmy Emelia Sitania; Tetra Hidayati; Saida Zainurossalamia Z A (Universitas Warmadewa, 2018)
A high turnover rate will have a negative impact on the organization. This can create instability and uncertainty on labor conditions and human resources improvement. The factors encouraging job satisfaction give effects to person's decision to move or quit. Given the fluctuating turnover intention rate in the last three years at IA Moeis Hospital, the purpose of this study was to determine the effect of equity compensation, work dedication, work absorption on turnover intention. Respondents in the study were honorary nurses at IA Moeis Hospital as many as 113 respondents. Data was analyzed by using SEM-Smart PLS version 3.37. The results showed that among five predetermined hypotheses made, there were two rejected, highlighting: there is a positive and insignificant impact of work dedication on turnover intention; and there is positive effect and no significant work absorption to honorary nurse turnover intention at IA Moeis Hospital Samarinda.